Laser therapy in the treatment of lesions to the inferior alveolar nerve (Research, Society and Development, 2021)
Inferior alveolar nerve damage is one of the most common complications in impacted third molar extractions. Nerve damage can lead to refractory hyperalgia, paresthesia and itching. Careful planning, through imaging exams such as computed tomography, in addition to anatomical knowledge of the nerve and careful tissue management, is essential to avoid complications. The diagnosis of neural deficit employs subjective methods through questionnaires and physical examination or more objectively with accurate examinations of nervous impulse conduction. The treatment is challenging, several surgical, drug and clinical modalities are applied, including the application of low-intensity laser. The objective of this work is to discuss the effectiveness of laser application through a review of the state-of-the-art literature. A search was performed in Medline, Pubmed and Academic Google databases, being selected based on the determined inclusion and exclusion criteria.